Buah Hutan Sumber Pangan dan Pengobatan di Kawasan Danau Toba, Indonesia - Aswandi Aswandi; Cut Rizlani Kholibrina (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2020)
Aswandi A, Kholibrina CR. 2020. Forest fruits for food and medicine in lake Toba region, Indonesia. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xxx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Indonesia's tropical forests are blessed with a high diversity of fruiting trees, a quarter can be consumed or contain medicinal properties. The objectives of study are to identify forest fruit trees that utilized by local community as food and traditional medicinal practices, botanical characteristics, phytopharmaca content and pharmacological activities. The research was conducted through exploration and in-depth interviews with 50 community respondents in Lake Toba, North Sumatra. Based on exploration of natural forests in Humbang Hasundutan and North Tapanuli, at least 21 forest fruit trees species were identified as potential food and medicine. Besides providing carbohydrates, forest fruits are source of essential vitamins and minerals. Some of these functional foods contain essential oils and utilized in traditional medicine. One is Rukam (Flacourtia rukam) which is mixed as a medicine for diarrhea and dysentery. Biwa (Eriobotya japonica) fruits contain citric acid, carotene, vitamins A, B and C. High potassium content is nutritious for controlling blood pressure, as well as copper and iron for erythrocytes formation. Traditionally, boiled-leave is utilized to reduce fever, while barks for roundworms treatment. Boiled-root is also utilized for bloating, stomach aches and diarrhea treatment. Furthermore, Harimunting (Rodomyrtus tomentosa) fruit extract contain anthocyanins which high antioxidant activity that increase haemoglobin. The leaves are utilized for diabetes and external wounds treatment. While, root extract is used to inhibit pus-causing bacteria development. Most of plant parts contain flavonoids, steroids, triterpenoids, tannins, quinones and essential elements including sodium, calcium, potassium and magnesium.